Transnational Marriage and Integration: Challenges and Adaptation Strategies of Indonesian Muslim Foreign Bride in Taiwan - Yuherina Gusman; Wildan Faisol; Sekar Ajeng Hapsari (UNIDA Gontor, 2024)
This study examines the obstacles and strategies Indonesian Muslim foreign brides encounter in Taiwan. Foreign brides frequently experience discrimination and are often classified as a social problem and the source of the Taiwanese populace's declining standards. The study used the qualitative method and gathered the data via in-depth interviews employing snowball sampling to select the participants. The interviews were conducted with ten informants residing in Taipei and New Taipei. This study employs integration theory to examine the interplay between four domains of integration: structural, social, cultural, and political and civil life. The study found that Muslim foreign brides encounter the most formidable obstacles within the realms of culture and society. Muslim foreign brides employ a strategic approach to confront these obstacles: solicit social support from the closest social circles, including the Muslim community at the Taipei Grand Mosque, the Indonesian Muslim community, and the Chinese Muslim Association. Additionally, they seek assistance from non-governmental organizations (NGOs) and other members of civil society. Keywords: Indonesian Foreign Bride, Integration, Muslim Foreign Bride, Taiwan, Transnational Marriage.